High-strength high-ductility Engineered/Strain-Hardening Cementitious Composites (ECC/SHCC) incorporating geopolymer fine aggregates. (January 2022) - Xu, Ling-Yu; Huang, Bo-Tao; Li, Victor C.; Dai, Jian-Guo
Abstract: In this study, Engineered/Strain-Hardening Cementitious Composites (ECC/SHCC) incorporating geopolymer fine aggregates were successfully developed with high strength and high ductility. A multi-scale investigation was conducted to gain an in-depth understanding of the microstructure and ductility enhancement mechanism of geopolymer aggregate ECC (GPA-ECC). The use of geopolymer fine aggregates enabled the high-strength ECC to achieve higher tensile ductility and finer crack width compared to existing ones with similar compressive strength in the literature. It was found that the GPA reacted with the cementitious matrix, and the width of the GPA/matrix interfacial transition zone (ITZ) was larger than that of the silica sand/matrix ITZ. Moreover, the GPA achieved a strong bond with the cementitious matrix and could behave as "additional flaws" in high-strength matrix, resulting in saturated multiple cracking and excellent tensile ductility of ECC. This study provides a new avenue for developing high-performance fiber-reinforced cementitious composites based on artificial geopolymer aggregates. Highlights: Geopolymer fine aggregates were successfully applied to develop high-strength high-ductility ECC with fine crack width. Geopolymer fine aggregates reacted with cementitious paste, resulting in a strong interfacial bond. Geopolymer fine aggregates acted as "additional flaws" in high-strength ECC matrix, leading to saturated multiple cracking. Compared with existing ambient-cured high-strength ECC, geopolymer aggregate ECC exhibited superior tensile ductility.